When is the best time to flower and disperse? A comparative analysis of plant reproductive phenology in the Mediterranean - Segrestin, Jules; Bernard-Verdier, Maud; Violle, Cyrille; Richarte, Jean; Navas, Marie-Laure; Garnier, Eric (Functional ecology, 2018)
The phenology of organisms corresponds to the temporal match between the components of their life cycle and the seasonal distribution of resources and hazards. Flowering has been extensively studied to describe the reproductive phenology of plants, but in comparison, other key events for reproductive success such as the seed maturation period and the time of seed dispersal have been considerably less investigated. This study describes the temporal sequence of onset of flowering and seed dispersal, and the time necessary to mature seeds in 138 species growing in the strongly seasonal climate of Mediterranean southern France. Data for the three traits were compiled from several original surveys to characterize the reproductive phenology of 47 annual, 67 perennial herbaceous and 24 low stature woody species. The timing of these three phases was assessed in relation to local climatic conditions, and the degree to which they were coordinated was tested. All three phenological traits spanned a wide range of values from early spring to late summer. Annuals flowered slightly earlier than perennials but the largest difference between these groups was found for the seed maturation period, which was much shorter in annuals. This resulted in earlier dispersal dates in these species, which occurred before periods of high water deficit. Significant positive correlations were found between onset of flowering, onset of seed dispersal and seed maturation period. This suggests a consistent pattern of coordination between the different phases of reproductive phenology across species. Our results show that while the time slot for flowering appears restricted to periods with adequate temperature and water availability for most species, the seed maturation period and dispersal phase can occur during periods of substantial water deficit, at least for perennials. They also suggest that the different species can be arrayed along a fast‐slow continuum based on reproductive events, from early flowering species with short seed maturation and early dispersal to late flowering species with long seed maturation and late dispersal. Whether this relates to the postulated fast‐slow continuum identified for the functioning of vegetative organs is a promising avenue for future research. A plain language summary is available for this article. Plain Language Summary